Visualizing urban and regional worlds: power, politics, and practices Afterword - Dorling, D; Hennig, B (SAGE Publications, 2015)
In this series of papers, presented as a theme issue of the journal Environment and Planning A, visualization has been used to explore a huge range of subjects. These range from trying to make clearer the powers that shape the urban landscape of the United States (Arribas-Bel and Gerritse, 2015) and further afield (Cattoor, 2015; Charlton et al, 2015; Swords and Jeffries, 2015), through to a better understanding of the geographies of wealth and power worldwide (Graham and De Sabbata, 2015; Hennemann et al, 2015), to rethinking old ways of mapping the flow of water (Hautdidier, 2015). So, how might all these issues be summed up in a conclusion? One answer is, of course, to draw yet more images: in this case images ranging from the world to local scale, and combining topography with hydrology in a very simple but hopefully useful way to try to sum up how we are beginning to see better that which until now we have only imagined and tried to describe to others in words. Visualization is about making visible what you imagine and even what you barely imagine but which is there in the data just waiting to be revealed.